ONSET OF CONNECTIONS BETWEEN THE PACIFIC AND ARCTIC OCEANS THROUGH THE BERING STRAIT IN THE NEOGENE - Gladenkov A.Yu.; Gladenkov Yu.B. (My University, 2004)
New data on the Neogene diatoms, mollusks, and magnetostratigraphy in the North Pacific and surrounding structures suggest the Bering Strait incipient opening in the latest Miocene or probably in the earliest Pliocene. Stratigraphic positions of oldest Arctic migrants in the Pacific sequences and of Pacific migrants in the Arctic sections are defined. Tectonic processes and eustatic fluctuations as possible causes of the strait opening are analyzed. The consequent changes in biota migration directions, oceanic circulation, and bioproductivity of planktonic groups are discussed.
Keywords: Neogene; Cenozoic::Neogene; Кайнозой::Неоген